2010
DOI: 10.1148/rg.303095101
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Energy CT: Clinical Applications in Various Pulmonary Diseases

Abstract: The dual-energy computed tomographic (CT) technique allows the differentiation of materials with large atomic numbers such as iodine and xenon. The basic principle of dual-energy CT is material decomposition based on attenuation differences at different energy levels. By using dual-energy CT angiography for the evaluation of perfusion defects in cases of pulmonary embolism, and using xenon CT for the evaluation of ventilation defects, it may be possible to replace perfusion and ventilation scanning. An iodine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
101
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(103 citation statements)
references
References 27 publications
0
101
0
2
Order By: Relevance
“…In traditional CT, X-ray generated by the X-ray tube has a continuous energy distribution called polychromatic X-ray. Since the introduction of CT, polychromatic 120-kVp X-rays have been widely used in clinical diagnosis as the standard acquisition in abdominal CT imaging [2][3][4][5][6].…”
mentioning
confidence: 99%
“…In traditional CT, X-ray generated by the X-ray tube has a continuous energy distribution called polychromatic X-ray. Since the introduction of CT, polychromatic 120-kVp X-rays have been widely used in clinical diagnosis as the standard acquisition in abdominal CT imaging [2][3][4][5][6].…”
mentioning
confidence: 99%
“…There is an increased interest in DE scanning, driven by the recent commercial availability of different DE hardware platforms (eg, dual-source CT and rapid kilovolt switching). 1 DE scanning, in general, offers 2 main advantages: material characterization based on the difference in material and tissue attenuation observed at 2 different photon energies; and non-material-specific image fusion combining low and high peak voltage acquisitions. 2 Material characterization proved beneficial for renal stone characterization, studying pulmonary perfusion through iodine distribution, and bone removal in CT angiography.…”
mentioning
confidence: 99%
“…Pontana et al [Pontana F , 2008] reported that the mean DLP of DECT pulmonary angiography for PE is 280 mGy *cm, corresponding to an average effective patient dose of about 5 mSv. Kang et al [Kang MJ, 2010] reported that the mean DLP of DECT with the PE protocol was 376 mGy*cm. All reported values for pulmonary DECT imaging are substantially lower than the reference value of 650 mGy*cm from the European guidelines on quality criteria for CT.…”
Section: Radiation Dosementioning
confidence: 99%